IT service catalog : a case study of the implementation need in a Pan-Nordic Insurance Company - Theppatipat, Trisai (My University, 2011)
IT service catalog is an increasingly important issue as many IT organizations have been realizing it as a central communication and visualization tool to bridge the gap between IT and the business. This study reviews relevant literature on IT service catalog and related issues on IT services delivery. Furthermore, the study shows how IT service catalog can enhance IT effectiveness as well as provide more benefits when integrating with Configuration Management Database. In order to analyze whether IT service catalog is needed to be implemented in a Pan-Nordic Insurance Company, this study also investigates the current IT services delivery of a case study. The findings of the study show the problems in the current situation of IT services delivery in the case. The characteristics of IT service catalog are recommended in order to help with the mentioned flaws.